Adsorption of fatty acid on beta-cyclodextrin functionalized cellulose nanofiber - Nor Hasmaliana, Abdul Manas; Nurhidayah Kumar, Muhammad Firdaus Kumar; Nurul Aqilah, Mohd Shah; Ling, Guang Yik; Nur Izyan, Wan Azelee; Siti Fatimah Zaharah, Mohd Fuzi; Nasratun, Masngut; Muhammad Abd Hadi, Bunyamin; Rosli, Md. Illias; El Enshasy, Hesham Ali (MDPI, 2023)
Fatty acids in wastewater contribute to high chemical oxygen demand. The use of cellulose nanofiber (CNF) to adsorb the fatty acids is limited by its strong internal hydrogen bonding. This study aims to functionalize CNF with β-cyclodextrin (β-CD) and elucidate the adsorption behaviour which is yet to be explored. β-CD functionalized CNF (CNF/β-CD) was achieved by crosslinking of β-CD and citric acid. Functionalization using 7% (w/v) β-CD and 8% (w/v) citric acid enhanced mechanical properties by increasing its thermal decomposition. CNF/β-CD was more efficient in removing palmitic acid, showcased by double adsorption capacity of CNF/β-CD (33.14% removal) compared to CNF (15.62% removal). CNF/β-CD maintained its adsorption performance after five cycles compared to CNF, which reduced significantly after two cycles. At 25 °C, the adsorption reached equilibrium after 60 min, following a pseudo-second-order kinetic model. The intraparticle diffusion model suggested chemical adsorption and intraparticle interaction as the controlling steps in the adsorption process. The maximum adsorption capacity was 8349.23 mg g−1 and 10485.38 mg g−1 according to the Sips and Langmuir isotherm model, respectively. The adsorption was described as monolayer and endothermic, and it involved both a physisorption and chemisorption process. This is the first study to describe the adsorption behaviour of palmitic acid onto CNF/β-CD.